Penerapan IPE dan IPC Pada Keluarga Dengan Rehabilitasi Stroke Di Kecamatan Percut Sei Tuan - Indrawati Indrawati; Soep Soep; Eqlima Elfira; Diah Lestari Nasution (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
The application of IPE and IPC refers to the opportunity for health professions to carry out care and training by involving other professions as partners. The method in this activity uses the lecture method, health checks, and stroke patient care training. This activity involves nutritionists, laboratory staff, nurses, environmental health and pharmacy who will help carry out community service activities in Percut Sei Tuan District. Participants in this activity after conducting field surveys and visiting directly and 8 family homes that have patients with stroke rehabilitation. Based on the activities carried out, it is recommended that patients do various things including controlling food nutrition, carrying out ROM (Range of Motion), increasing a healthy lifestyle with